Un ejemplo de la heráldica leonesa del siglo XIII. El sello de Inés Fernández - Torre Sevilla-Quiñones de León, Margarita (Estudios humanísticos. Geografía, historia y arte, 1995)
This study tries to be a first approach to medieval heraldry in the Kingdom of León. It’s based on a sealing mould, dated in XIII century, which was found in Villamayor de Campos. The owner of this seal was a member of Count Ponce de Cabrera’s family: Inés Fernández. The identification of this woman was possible through a combination of two factors: the coat of arms and the inscription. This is a good example to know how heraldry turns to be one of the most representative elements of noble mentality.